Oligomer saccharide reduction during dilute acid pretreatment co-catalyzed with Lewis acids on corn stover biomass - Degenstein, John; Kamireddy, Srinivas Reddy; Tucker, Melvin P.; Ji, Yun (International Journal of Agricultural and Biological Engineering, 2013)
The dilute sulfuric acid pretreatment of lignocellulosic biomass is a well understood process that significantly enhances the yield of glucose after enzymatic saccharification. The goal of this research was to perform a systematic study to evaluate the yield of fermentable sugars during dilute sulfuric acid pretreatment that is co-catalyzed with the transition metal Lewis acid salts: AlCl3, FeCl2, FeCl3, and La(OTf)3. All Lewis acids apart from FeCl2 reduced the presence of xylo-oligomers by a large margin when compared to the non-co-catalyzed control sample pretreatments. The presence of these xylo-oligomers acts as inhibitors during enzymatic saccaharification step. The Lewis acids AlCl3, FeCl3, and La(OTf)3 were also able to marginally increase the overall enzymatic digestibility specifically for corn stover pretreated at 160°C with 10 mM of Lewis acids. The hard Lewis acid such as AlCl3 increased the formation inhibitory products such as furfural and 5-hydroxymethylfurfural (HMF). There was good correlation between reduction of xylo-oligomers and increased concentration furfural with increase in Lewis acid hardness.